2015
DOI: 10.1039/c5ra11838g
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of perfluorosulfonic short side chain polymer membranes

Abstract: Perfluorinated short side chain membranes synthesized by novel aqueous emulsion method demonstrate specific structure dependent on the chemical composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…In membranes obtained earlier by pressing, it also rises from 3.5 to 4.7-4.8 nm. 40 Thus, on a scale of up to 5 nm (the distance between adjacent water-conducting channels in the bundle), there is no significant difference between membranes obtained by different methods (pressing and casting). The crystallinity area, which characterizes the mutual packing of the channel bundles, in cast membranes, as compared to pressed membranes, is much better expressed, and shifted to smaller scales (10-15 nm vs. 17-22 nm).…”
Section: Comparing the Properties And Structure Of Aquivion ® -Type M...mentioning
confidence: 97%
See 1 more Smart Citation
“…In membranes obtained earlier by pressing, it also rises from 3.5 to 4.7-4.8 nm. 40 Thus, on a scale of up to 5 nm (the distance between adjacent water-conducting channels in the bundle), there is no significant difference between membranes obtained by different methods (pressing and casting). The crystallinity area, which characterizes the mutual packing of the channel bundles, in cast membranes, as compared to pressed membranes, is much better expressed, and shifted to smaller scales (10-15 nm vs. 17-22 nm).…”
Section: Comparing the Properties And Structure Of Aquivion ® -Type M...mentioning
confidence: 97%
“…When saturated with water, the characteristic distance between the bundles of channels for membranes obtained by casting methods practically disappears; channel bundles are distributed almost uniformly on a scale of 6-40 nm (Figure 8), while crystallinity in pressed membranes preserves in most cases. 34,40 Thus, we have shown that the method of membrane manufacturing (pressing or casting) significantly affects the internal fine structure of Aquivion ® -type membranes, without violating the characteristics of the basic structural elements of membrane (channels). This is reflected in the electrochemical and mechanical properties of the original non-stretched membranes, giving an advantage to cast membranes over pressed ones.…”
Section: Comparing the Properties And Structure Of Aquivion ® -Type M...mentioning
confidence: 99%
“…Structural studies of dry and hydrated membranes of the Aquivion type were carried out using small‐angle neutron scattering (SANS) 118,119 . This technique allowed revealing peculiarities of membranes' fine structure, formed by a system of ordered proton conducting channels in perfluorinated polymer matrix.…”
Section: From the Synthesis Of Short‐side‐chain Fluorinated Ionomers mentioning
confidence: 99%
“…With the aim of overcoming some limitations of Nafion ® when it operates in more drastic conditions, such as high temperature and low relative humidity, a short-side-chain ionomer can be used. In particular, Aquivion ® , developed by Solvay Specialty Polymers, is a short-side-chain (SSC) perfluorosulfonic polymer and presents a higher crystallinity, higher glass-transition temperature (T g ) and lower swelling than Nafion ® together with a high proton conductivity, making this SSC polymer more suitable to work in a PEMFC at higher cell temperature and lower relative humidity levels (RH, %) [22][23][24][25][26]. Talukdar et al observed a correlation between the composition of the ionomer and the durability, with SSC polymer being chemically less stable than long-side-chain polymer [27].…”
Section: Introductionmentioning
confidence: 99%